Functional capacity and associated factors among longevous senior individuals living in community: a population study in Northeastern Brazil - Thaís Alves Brito; Marcos Henrique Fernandes; Raildo da Silva Coqueiro; Cleber Souza de Jesus; Roberta Freitas (Universidade de São Paulo, 2014)
The objective of this study was to determine the prevalence of impaired functional capacity and the associated factors in longevous elderly individuals from a city in the countryside of Northeastern Brazil. This is a cross-sectional, population- and community-based study. The research population consisted of senior citizens aged ≥80 years old, residents of the urban area of Lafaiete Coutinho, Bahia, Brazil. Data were collected in the households through a questionnaire with information on functional, socioeconomic, and demographic aspects and health/behavioral factors. Data analysis was performed using multinomial logistic regression at a significance level of 5%. A total of 94 senior citizens, whose average age was 86.1 years old (±6.39), whereof 59.6% were female, were interviewed. Among the longevous senior individuals, 19.1% were considered independent to instrumental and basic activities of daily living, whereas 56.2% were considered as dependent to instrumental activities of daily living, and 24.7% to both basic and instrumental activities of daily living. There has been an association between impaired functional capacity, both for basic and instrumental activities of daily living, and the variables referring to sex and drug use; another one was between race/color and instrumental activities of daily living dependence. We got to the conclusion that there was high prevalence (80.9%) of longevous senior citizens who depend on instrumental and basic activities of daily living. Also, the impairment of functional capacity on longevous senior citizens was associated with female sex, non-white race/color, and use of one or more drugs.